2014
DOI: 10.1371/journal.pone.0102738
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction with Cardiolipin Triggers Functional Activation of Dynamin-Related Protein 1

Abstract: Dynamin-Related Protein 1 (Drp1), a large GTPase of the dynamin superfamily, is required for mitochondrial fission in healthy and apoptotic cells. Drp1 activation is a complex process that involves translocation from the cytosol to the mitochondrial outer membrane (MOM) and assembly into rings/spirals at the MOM, leading to membrane constriction/division. Similar to dynamins, Drp1 contains GTPase (G), bundle signaling element (BSE) and stalk domains. However, instead of the lipid–interacting Pleckstrin Homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
145
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 72 publications
(94 reference statements)
19
145
1
Order By: Relevance
“…Taken together, these results suggest that maintaining the net negative charge of the vesicles is not the only parameter affecting Drp1 membrane binding but that the intrinsic monolayer curvature of the lipids also plays a role. Therefore, and contrary to what is believed in the field (49,50), our results show that CL is not essential for Drp1 binding to membranes. Indeed, Drp1 also catalyzes peroxisomal division (10,56), suggesting that a common mechanism exists for mitochondrial and peroxisomal division.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Taken together, these results suggest that maintaining the net negative charge of the vesicles is not the only parameter affecting Drp1 membrane binding but that the intrinsic monolayer curvature of the lipids also plays a role. Therefore, and contrary to what is believed in the field (49,50), our results show that CL is not essential for Drp1 binding to membranes. Indeed, Drp1 also catalyzes peroxisomal division (10,56), suggesting that a common mechanism exists for mitochondrial and peroxisomal division.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we show that GTP induced a compact assembly of Drp1 on the membrane surface, in contrast to the homogeneous distribution of the protein on the GUVs in the absence of nucleotides. These clusters are also found on flat and curved membranes and are likely related to Drp1 scaffolding because GTP and GTP analogs have been shown to induce Drp1 oligomerization (29,31,49,71). Therefore, our results reveal two distinct modes of curvature-independent Drp1 binding to membranes that set it apart from other members of the dynamin family and that may be relevant for the molecular mode of action of Drp1 in the context of the cell.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The middle and GED domains promote Drp1 self-assembly, which is also critical for its role in facilitating mitochondrial fission (18,19). In vitro, the addition of negatively charged lipids increases Drp1 self-assembly to form larger helical assemblies that represent the contractile apparatus of mitochondrial fission (20), and these functional polymers exhibit stimulated GTPase activity (14,(21)(22)(23). The VD has recently been shown to act as a negative regulator of Drp1 self-assembly (14) with an inherent ability to interact with cardiolipin (CL) present in mitochondrial membranes (21,(23)(24)(25).…”
mentioning
confidence: 99%
“…In vitro, the addition of negatively charged lipids increases Drp1 self-assembly to form larger helical assemblies that represent the contractile apparatus of mitochondrial fission (20), and these functional polymers exhibit stimulated GTPase activity (14,(21)(22)(23). The VD has recently been shown to act as a negative regulator of Drp1 self-assembly (14) with an inherent ability to interact with cardiolipin (CL) present in mitochondrial membranes (21,(23)(24)(25). Studies in yeast have shown that the VD is required for interactions with a mitochondrial adaptor protein (26), but the partner protein identified in that study is not conserved in higher eukaryotes, which suggests that the role of the VD may have evolved in higher organisms to accommodate different regulatory interactions in the cytosol and at the surface of mitochondria.…”
mentioning
confidence: 99%